Repeated attacks of type III hereditary angioedema with factor XII mutation during pregnancy. (November 2018) - Feray, S.; Fain, O.; Kayem, G.; Sabourdin, N.; Constant, I.; Rigouzzo, A.
Highlights: Type III hereditary angioedema (HAE III) with Factor XII mutation is rare. Both levels and function of C1-inhibitor are normal. HAE III may be oestrogen-dependent and is aggravated during pregnancy. Aggravation during pregnancy is more often observed in women with a FXII mutation. Pregnant women may benefit from the administration of C1-inhibitor concentrate. Abstract: In type III hereditary angioedema (HAE type III), the phenotype is the same as type I and type II disease, but the level and function of C1-esterase inhibitor (C1-INH) is normal. Hereditary angioedema type III has been described as an oestrogen-sensitive form because it can be triggered or aggravated by exposure to high oestrogen levels as seen during pregnancy, especially when associated with Factor XII mutation. This case report describes the evolution and management of repeated angioedema attacks during pregnancy in a woman with HAE, with normal levels and function of C1-INH (type III); and a mis-sense mutation of factor XII. The physiopathology and genetic features, the unpredictability of clinical manifestations and the management during pregnancy and delivery are discussed.